Effect of substrate tilt angle on morphological, structural and optical properties of Zinc Oxide thin film - Lee, Benjamin Kun Ze (2015)
This paper studies the morphological, structural and optical properties of zinc oxide thin film sputtered at different substrate tilt angle. These thin films were grown using radio frequency magnetron sputtering and characterised by scanning electron microscope, X-ray diffraction and ultraviolet-visible spectrophotometer. Observations from scanning electron microscope shows compact, inclined columnar structures of deposited zinc oxide particles. Compactness of deposited zinc oxide and inclination angle of the columnar structures increases with increasing substrate tilt angle. From X-ray diffraction analysis, an increasing trend of zinc oxide to tin oxide crystallite size ratio was obtained as substrate tilt angle increases, implying release of micro strains and generation of defects have higher chances of occurrence with increasing substrate tilt angle. From ultraviolet-visible spectroscopy, substrate tilt angle shows no significant effect on the absorption ability of zinc oxide thin film except for zinc oxide thin film sputtered at substrate tilt angle of 40°. The deviation may be due to deposited film being the thickest and the roughest at substrate tilt angle of 40° resulting in the a different optical property as compared to the rest of the zinc oxide film sputtered at other angles from 0° to 80° .